Regulation of c-Jun NH(2)-terminal Kinase ( Jnk) Gene Expression during T Cell Activation - Weiss, Linda (The Rockefeller University Press, 2000)
The c-Jun NH(2)-terminal kinases (JNKs) are a group of mitogen-activated protein (MAP) kinases that participate in signal transduction events mediating specific cellular functions. Activation of JNK is regulated by phosphorylation in response to cellular stress and inflammatory cytokines. Here, we demonstrate that JNK is regulated by a second, novel mechanism. Induction of Jnk gene expression is required in specific tissues before activation of this signaling pathway. The in vivo and in vitro ligation of the T cell receptor (TCR) leads to induction of JNK gene and protein expression. TCR signals are sufficient to induce JNK expression, whereas JNK phosphorylation also requires CD28-mediated costimulatory signals. Therefore, both expression and activation contribute to the regulation of the JNK pathway to ensure proper control during the course of an immune response.